The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.cognition.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

What we say and what we do: The relationship between real and hypothetical moral choices

Abstract: Highlights► We show people are unable to appropriately judge outcomes of moral behaviour. ► Moral beliefs have weaker impact when there is a presence of significant self-gain. ► People make highly self-serving choices in real moral situations. ► Real moral choices contradict responses to simple hypothetical moral probes. ► Enhancing context can cause hypothetical decisions to mirror real moral decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
190
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(201 citation statements)
references
References 28 publications
7
190
1
3
Order By: Relevance
“…For example, there is evidence that children say they will give more in a Dictator Game than what they actually give (Blake, 2018). Another study showed that young adults kept slightly more money for themselves in a real versus hypothetical economic game in which a confederate receives electric shocks when the participant keeps money for themselves (FeldmanHall et al., 2012). Findings in this area are not entirely consistent: one study with adults found that the amount given in a Dictator Game with hypothetical money was very similar to the amount given in a game with real money (Ben‐Ner, Kramer, & Levy, 2008), although this relationship varied depending on the personality traits extraversion and agreeableness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence that children say they will give more in a Dictator Game than what they actually give (Blake, 2018). Another study showed that young adults kept slightly more money for themselves in a real versus hypothetical economic game in which a confederate receives electric shocks when the participant keeps money for themselves (FeldmanHall et al., 2012). Findings in this area are not entirely consistent: one study with adults found that the amount given in a Dictator Game with hypothetical money was very similar to the amount given in a game with real money (Ben‐Ner, Kramer, & Levy, 2008), although this relationship varied depending on the personality traits extraversion and agreeableness.…”
Section: Discussionmentioning
confidence: 99%
“…In a more realistic setting, a recent study (FeldmanHall et al, 2012) used a pain-versus-gain paradigm to show that in the face of contextually salient motivational cues (like monetary gain) people were ready to let others get physically hurt, which contrasts starkly with the previous research showing that aversion to harming others is one of the most deeply ingrained of moral intuitions (Cushman, Young, & Hauser, 2006;Haidt, 2007). They also showed that the behavior of participants in real life increasingly deviated away from the judgment they made as the presentation of moral situations became increasingly contextually impoverished.…”
mentioning
confidence: 99%
“…Neste estudo usou-se uma vinheta clínica retratando o caso de um adolescente com problemas de abuso de ál-cool. O recurso a esta estratégia pode ser considerado uma mais-valia porque facilita a avaliação, permitindo a obtenção de respostas mais aproximadas ao que seria o comportamento dos adolescentes em situações reais, ao passo que, quando é usada uma situação hipotética mais simples, as respostas dos participantes não costumam re etir as decisões que eles teriam no seu dia-adia (FeldmanHall et al, 2012). Os resultados obtidos sugerem-nos alguns comentári-os: Das várias componentes da LSM, o reconhecimento do problema emerge como um fator inicial e importante, pois é o primeiro passo para a procura de ajuda de fontes pro ssionais (Gulliver, Gri ths & Christensen, 2010).…”
Section: Discussão Dos Resultadosunclassified